Joom Jak Sasi: The Role of Women in Traditional Coastal Management in Aduwei Raja Ampat - Kabes, Yustina Priskila Patricia (Analisa: Journal of Social Science and Religion, 2025)
This article explores the Joom Jak Sasi, a community group led by indigenous women practicing traditional coastal management known as Sasi in Aduwei, Raja Ampat. Drawing on the customary Sasi system, which regulates the use of natural resources through seasonal closures. This research highlights how gender, tradition, and religion intersect to promote sustainable environmental management. Once a male-dominated domain, Sasi in Aduwei has been increasingly influenced by female leadership, particularly through the Joom Jak Sasi group established in 2022. This research examines how these women negotiate patriarchal structures while promoting inclusive ecological governance, contributing to community empowerment and biodiversity protection. These research findings show that Indigenous women act as cultural and ecological guardians, challenging traditional gender hierarchies while revitalizing local knowledge systems. Furthermore, the integration of customary, religious, and scientific conservation efforts has contributed to more equitable and effective management of marine resources. By centering the role of women in environmental conservation, Joom Jak Sasi women not only conserve natural ecosystems but also redefine leadership roles and strengthen cultural identities in the face of ecological and social change.